Hearing-impaired specialized career education: does it benefit the hospitality industry?/ Norhayati Mohd Yusof...[et al.] - Mohd Yusof, Norhayati; Mohd Zahari, Mohd Salehuddin (Faculty of Hotel Management and Tourism, Universti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
For many years, disabled graduates particularly with impaired hearing have been accepted as key equity group on the basis that their overall participation levels are limited to specialised education to equip them for certain type of employment. This scenario is also occurring in Malaysia with a number of tertiary institutions offering specialised career education including the hospitality program. The numbers of these graduates are increasing, but there are still a large number of them who are excluded from employment. What may cause for such situation is yet to be investigated. Therefore, this paper attempts to review the development of special education in Malaysia, the employability of disabled persons at global scenario, and highlighting the issues of hearing impairment graduates and their employability in Malaysia hence subsequently proposed for further investigation.